A 3T Phase-Sensitive Inversion Recovery MRI Sequence Improves Detection of Cervical Spinal Cord Lesions and Shows Active Lesions in Patients with Multiple Sclerosis - Fechner, A.; Savatovsky, J.; El Methni, J.; Sadik, J.C.; Gout, O.; Deschamps, R.; Gueguen, A.; Lecler, A. (American Journal of Neuroradiology, 2019)
BACKGROUND AND PURPOSE: Magnetic Resonance Imaging is the modality of choice to detect spinal cord lesions in patients with Multiple Sclerosis (MS). However, this imaging is challenging. New sequences such as phase-sensitive inversion recovery have been developed to improve detection. Our aim was to compare a 3D phase-sensitive inversion recovery and a conventional imaging dataset including postcontrast T2WI and T1WI to detect MS spinal cord lesions.MATERIALS AND METHODS: This retrospective single-center study included 100 consecutive patients with MS (mean age, 41 years) from January 2015 to June 2016. One senior neuroradiologist and 1 junior radiologist blinded to clinical data checked for new spinal cord lesions, individually analyzing conventional and 3D phase-sensitive inversion recovery datasets separately, placing a 3-week delay between the 2 readings. A consensus reading was done with a third senior neuroradiologist. A Wilcoxon test was used to compare the 2 imaging datasets. Intra- and interobserver agreement was assessed by the κ coefficient.RESULTS: 3D phase-sensitive inversion recovery detected significantly more lesions than conventional imaging (480 versus 168, P < .001). Eleven patients had no detected lesions on T2WI, whereas 3D phase-sensitive inversion recovery detected at least 1 lesion. All postcontrast T1WI enhancing lesions were also visible on 3D phase-sensitive inversion recovery. The signal-to-noise ratio was significantly higher using 3D phase-sensitive inversion recovery (0.63 versus 0.46, P = .03). Mean reading confidence was significantly higher using 3D phase-sensitive inversion recovery. Inter- and intraobserver agreement was good for both datasets.CONCLUSIONS: Our study showed that 3D phase-sensitive inversion recovery significantly improved detection of cervical spinal cord lesions, including both enhancing and nonenhancing lesions in patients with MS.CNRcontrast-to-noise ratioPSIRphase-sensitive inversion recoveryMAGNIMSMagnetic Resonance Imaging in Multiple SclerosisMERGEMulti-Echo Recombined Gradient EchoPST1-IRphase-sensitive T1-weighted inversion-recovery MR imaging